2001
DOI: 10.1164/ajrccm.164.4.2010170
|View full text |Cite
|
Sign up to set email alerts
|

Role of CD4+CD25+Regulatory T Cells in T Helper 2 Cell-mediated Allergic Inflammation in the Airways

Abstract: It has recently been shown that CD4(+) CD25(+) T cells are immunoregulatory T cells that prevent CD4(+) T cell-mediated organ-specific autoimmune diseases. To determine whether CD4(+) CD25(+) T cells downregulate Th2 cell-mediated allergic inflammation in the airways, we studied antigen-induced eosinophil recruitment in the airways in BALB/c Rag-2(-)(/-) mice transferred with CD4(+) CD25(+) T cell-depleted or unfractionated T cells from ovalbumin-specific TCR transgenic mice. Antigen-induced eosinophil recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
78
1
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(86 citation statements)
references
References 34 publications
6
78
1
1
Order By: Relevance
“…Conceivably, CD4 ؉ CD25 ؉ T cells may influence either the maturation of Th2 cells directly or act by inhibiting Th1 development (i.e., cross-regulation). Using the DO11.10 model of airway inflammation, it has been suggested that regulatory T cells favor Th2 polarization by inhibiting Th1 development (35). However, in our experiments, the Th2 cells prepared from CD4 ϩ CD25 Ϫ T cells did not produce any detectable IFN-␥, even after adoptive transfer into mice that were then repeatedly exposed to OVA aerosols.…”
Section: Discussioncontrasting
confidence: 74%
“…Conceivably, CD4 ؉ CD25 ؉ T cells may influence either the maturation of Th2 cells directly or act by inhibiting Th1 development (i.e., cross-regulation). Using the DO11.10 model of airway inflammation, it has been suggested that regulatory T cells favor Th2 polarization by inhibiting Th1 development (35). However, in our experiments, the Th2 cells prepared from CD4 ϩ CD25 Ϫ T cells did not produce any detectable IFN-␥, even after adoptive transfer into mice that were then repeatedly exposed to OVA aerosols.…”
Section: Discussioncontrasting
confidence: 74%
“…This indicates that Treg not only suppress Th1 responses (61) but are also critical to control Th2 cytokine production in normal conditions (13). Conversely, the fact that PC61 pretreatment led to decreased IL-4 and IL-13 production in offspring born of asthmatic mothers indicates that Treg, in pathological conditions, can promote local Th2 cytokine imbalance in newborn as previously observed in adult mice (62).…”
Section: Discussionmentioning
confidence: 64%
“…Their suppressive activity both in vitro and in vivo appears to be mediated by several mechanisms depending on the model used and includes cell-to-cell contact (27,36,37) and the release of IL-10 (9, 38) and 39,40). A possible mechanism of suppression in humans is the cytolytic activity of CD4 ϩ CD25 ϩ regulatory T cells that are granzyme-and perforin-mediated (41).Although the regulatory profiles of CD4 ϩ CD25 ϩ T cells have been described in mouse models of allergen-induced AHR and airway inflammation (9,34,35), the mechanisms that direct the functional activation of these regulatory activities have not been well defined. In the present study, we investigated the role of MHC I on naturally occurring CD4 ϩ CD25 ϩ regulatory T cells (nTregs) and the requirement for interaction with CD8 in the lung and show that interactions between MHC I and CD8 are essential for the expression of the immunoregulatory properties of nTregs on lung allergic responses.…”
mentioning
confidence: 99%
“…Although the regulatory profiles of CD4 ϩ CD25 ϩ T cells have been described in mouse models of allergen-induced AHR and airway inflammation (9,34,35), the mechanisms that direct the functional activation of these regulatory activities have not been well defined. In the present study, we investigated the role of MHC I on naturally occurring CD4 ϩ CD25 ϩ regulatory T cells (nTregs) and the requirement for interaction with CD8 in the lung and show that interactions between MHC I and CD8 are essential for the expression of the immunoregulatory properties of nTregs on lung allergic responses.…”
mentioning
confidence: 99%
See 1 more Smart Citation